Conscientious objection - a cross-sectional, vignette-based, mixed methods exploration of Australian pharmacists' perspectives - Sami Isaac; Ardalan Mirzaei; Andrew J. McLachlan; Betty B. Chaar (Taylor & Francis Group, 2024)
ABSTRACTBackground: Conscientious objection (CO) in healthcare is a controversial topic. Some perceive CO as freedom of conscience, others believe their professional duty-of-care overrides personal-perspectives. There is a paucity of literature pertaining to pharmacists' perspectives on CO.Aim: To explore Australian pharmacists' decision-making in complex scenarios around CO and reasons for their choices.Method: A cross-sectional, qualitative questionnaire of pharmacists' perspectives on CO. Vignette-based questions were about scenarios related to medical termination, emergency contraception, IVF surrogacy for a same-sex couple and Voluntary Assisted Dying (VAD)Results: Approximately half of participants (n = 223) believed pharmacists have the right to CO and most agreed to supply prescriptions across all vignettes. However, those who chose not to supply (n = 20.9%), believed it justifiable, even at the risk of patients failing to access treatment. Strong self-reported religiosity had a statistically significant relationship with decisions not to supply for 3 of 4 vignettes. Three emergent themes included: ethical considerations, the role of the pharmacist and training and guidance.Conclusion: This exploratory study revealed perspectives of Australian pharmacists about a lack of guidance around CO in pharmacy. Findings highlighted the need for future research to investigate and develop further training and professional frameworks articulating steps to guide pharmacists around CO.